Solution-Oriented media management research: a framework to nurture future impact of the field. Issue 4 (2nd October 2022) - Petzold, Thomas; Knuth, Ingo
ABSTRACT: This article assesses the ways in which media management research collaborates with companies in the fields of media & technology, marketing, and market research. It examines various modes of collaboration, and how they contribute towards a scholar-industry-collaboration with impact. Our conceptualization divides academic research into basic research, use-inspired, applied research and solution-oriented. Building furthermore on existing research across various fields in management studies we develop a novel framework for the assessment of scholar-industry-collaborations. To test our framework, we examine media management research output over the timespan of ten years – a total of 557 academic publications and 246 industry research publications enriched with additional data. We assigned each article to one of the four categories in our framework (basic, use-inspired, applied, solution-oriented), and then further examined them against more finely tuned content criteria to allow for further insights. The analysis of 803 studies revealed a low collaborative relationship between media management scholars and the industry. More strikingly, there is an obvious lack of solution-oriented research. We argue that solution-oriented research has significant potential to recalibrate media management research in scope and scale as its very purpose is to generate synergetic impact for both academia as well as society at large.